Modification of imidazothiazole derivatives gives promising activity in B-Raf kinase enzyme inhibition; synthesis, in vitro studies and molecular docking - Ammar, Usama M.; Abdel-Maksoud, Mohammed S.; Mersal, Karim, I; Ali, Eslam M. H.; Yoo, Kyung Ho; Choi, Hong Seok; Lee, Jae Kyun; Cha, Sun Young; Oh, Chang-Hyun (Pergamon Press Ltd., 2020)
B-Raf mutation was identified as a key target in cancer treatment. Based on structural features of dabrafenib (potent FDA approved B-Raf inhibitor), the design of new NH2-based imidazothiazole derivatives was carried out affording new highly potent derivatives of imidazothiazole-based scaffold with amino substitution on the terminal phenyl ring as well as side chain with sulfonamide group and terminal substituted phenyl ring. In vitro enzyme assay was investigated against V600E B-Raf kinase. Compounds 10l, 10n and 10o showed higher inhibitory activities (IC50 = 1.20, 4.31 and 6.21 nM, respectively). In vitro cytotoxicity evaluation was assessed against NCI-60 cell lines. Most of tested derivatives showed cytotoxic activities against melanoma cell line. Compound 10k exhibited most potent activity (IC50 = 2.68 mu M). Molecular docking study revealed that the new designed derivatives preserved the same binding mode of dabrafenib with V600E B-Raf active site. It was investigated that the new modification in the synthesized derivatives (substituted with NH2) had a significant inhibitory activity towards V600E B-Raf. This core scaffold is considered a key compound for further structural and molecular optimization.
Keywords: DISCOVERY; PATHWAY; DESIGN; SERIES